Pandangan Hukum Islam Terhadap Ganti Rugi dalam Pengadaan Tanah yang Dipergunakan untuk Kepentingan Umum - Lidia Fathaniyah; Istianah Istianah; Wage Wage; Encep Saepudin (Proceedings Series on Social Sciences & Humanities, 2022)
This article examines the view of Islamic law on compensation in land acquisition for the public interest. This research was conducted to find out how Islamic law views compensation in land acquisition for the public interest. The method used is literature research method with a normative juridical approach, namely by examining Islamic law related to the theme and examining various literatures that have a relationship with the theme under study. Compensation in land acquisition is an important thing because usually other parties will force their will to continue to carry out land acquisition even though the land authority does not agree with it on the grounds that the compensation is not equal to the value of the land and sometimes there is no agreement between the parties concerned and the matter it will create a loss problem. The result of this study based on the Qur’an, the prophet’s message and the MUI fatwa are that the view of Islamic law on compensation in land acquisition for the public interest is permissible on the condition that it is in accordance with Islamic law by way of deliberation and determining an appropriate and reasonable price. After an agreement is made, then the transfer of property rights, this transfer is through the process of buying and selling, waqf, and exchange.